The Portrayal of Women in Social Media: Implications for Social Work Practice - Gowda, Manasa (Universitas Islam Indonesia, 2024)
​This study explores the portrayal of women on social media and its implications for gender representation, empowerment, and social work practice. It investigates how digital platforms simultaneously perpetuate stereotypes and foster spaces for resistance and advocacy. Using qualitative content analysis, data were collected from Instagram, Twitter, Facebook, and TikTok to examine recurring themes in visual and textual portrayals of women. The analysis identified four dominant categories—body image, gender stereotypes, empowerment, and activism—revealing the paradox of social media as both a site of self-objectification and a medium for feminist expression. Findings indicate that while idealized portrayals reinforce unrealistic beauty standards and psychological strain, movements such as #MeToo and #BodyPositivity redefine empowerment and visibility in digital spaces. The study further highlights how intersectionality and algorithmic bias which influence women’s voices are amplified or silenced online, emphasizing the persistence of structural inequalities within digital environments. Integrating social work and media literacy emerges as a transformative approach to fostering critical awareness, resilience, and ethical engagement. Overall, the research contributes to feminist digital scholarship by illuminating the complex interplay between empowerment, inequality, and representation, urging policymakers, educators, and practitioners to promote inclusive, equitable, and socially conscious media practices that advance gender justice in the digital age.​